Synthesis and diatropicity of trans-2′,5′,10b,10c-tetramethylfurano[3,4-e]-10b,10c-dihydropyrene. A valence isomerization to form a novel isoannulenofuran at the expense of two benzene and one furan rings - Lai, Y.-H. (2014)
Journal of Organic Chemistry